Serum BPIFB4 levels classify health status in long-living individuals. Issue 1 (December 2015) - Villa, Francesco; Malovini, Alberto; Carrizzo, Albino; Spinelli, Chiara; Ferrario, Anna; Maciąg, Anna; Madonna, Michele; Bellazzi, Riccardo; Milanesi, Luciano; Vecchione, Carmine; Puca, Annibale
Abstract Background People that reach extreme ages (Long-Living Individuals, LLIs) are object of intense investigation for increase/decrease of genetic variant frequencies, genetic methylation levels, protein abundance in serum and tissues. The aim of these studies is the discovery of the mechanisms behind LLIs extreme longevity and the identification of markers of well-being. We have recently associated a BPIFB4 haplotype (LAV) with exceptional longevity under a homozygous genetic model, and identified that CD34+ of LLIs subjects express higher BPIFB4 transcript as compared to CD34+ of control population. It would be of interest to correlate serum BPIFB4 protein levels with exceptional longevity and health status of LLIs. Methods Western blots on cellular medium to detect BPIFB4 secretion in transfected HEK293T cells with plasmid carrying BPIFB4 and ELISA on LLIs serum to detect BPIFB4 levels. Results Here we show that BPIFB4 is a secreted protein and its levels are increased in serum of LLIs, and high BPIFB4 levels classify their health status. Conclusions Serum BPIFB4 protein levels classify longevity and health status in LLIs. Further studies are required to evaluate the possible role of BPIFB4 in monitoring disease progression.